2021
DOI: 10.1128/msystems.01161-20
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Microevolution of Vibrio parahaemolyticus Populations in Shellfish Farms

Abstract: Vibrio parahaemolyticus is becoming the leading cause of acute bacterial gastroenteritis, but its population dynamics in aquafarms have received limited attention. To address this research gap, we selected three shellfish farms to examine the impacts of ocean currents and the transport of live aquatic animals on the transmission and microevolution of V. parahaemolyticus by using multilocus sequence typing (MLST) and whole-genome sequencing. MLST and genomic analysis revealed that the community structure of V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…We described the results by grouping STs to observe genomic variations. ST114 isolates from five locations were geographically distinct (Figure 3b), of which Yingkou isolates were clustered with Dalian isolates identified in our previous study (Fu et al, 2021b). Relative to other Yingkou isolates, VP14-2020 had only one SNP.…”
Section: Phylogenetic Of V Parahaemolyticus Isolates In Four Farmsmentioning
confidence: 64%
See 2 more Smart Citations
“…We described the results by grouping STs to observe genomic variations. ST114 isolates from five locations were geographically distinct (Figure 3b), of which Yingkou isolates were clustered with Dalian isolates identified in our previous study (Fu et al, 2021b). Relative to other Yingkou isolates, VP14-2020 had only one SNP.…”
Section: Phylogenetic Of V Parahaemolyticus Isolates In Four Farmsmentioning
confidence: 64%
“…Intensive aquacultural activities in traditional farms might also provide a suitable niche for HGT between Vibrio spp. and other bacteria (Fu et al, 2021b). However, there is no long‐term surveillance on V .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the differences in taxonomic diversity of respiratory microbiota in lung cancer and benign pulmonary lesion tissues were analyzed. ANOSIM (analysis of similarities) is mainly used to analyze inter-group similarity of high-dimensional data and provide a basis for inter-group difference evaluation ( 21 ). ANOSIM suggested that significant differences existed in LUSC, LUAD, and BPD groups ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, four strains of V. parahaemolyticus displayed resistance to amoxicillin, cephalothin, erythromycin, and streptomycin, whereas one remaining strain of V. vulnificus exhibited resistance to oxolinic acid, flumequine, and sulfadiazine (Scarano et al., 2014). It has also been demonstrated that the transport of shellfish from one farm to another had been proven to favor the transmission and microevolution of V. parahaemolyticus populations due to genomic exchanges (Fu et al., 2021a). However, the stocking density is a critical point in industry, in which balance between productivity and operational costs is essential to ensure both animals health and welfare, as well as the economic well‐being of the company.…”
Section: Sources and Contamination Routes Of Raw Seafoodmentioning
confidence: 99%